"In the secret chambre of the mynde, in the preuy closet of the sowle": monastic discipline and devotion in More's Life of Pico. Issue 1 (June 2017) - Alakas, Brandon
Abstract : Already present in certain biographical details, Thomas More's programmatic efforts to create new patterns of mixed living are most innovatively employed in the Life of Pico . In creating a vernacular translation of Gianfrancesco's Vita Ioannis Pici Mirandulae, More executes substantial changes that draw attention to Pico's strong desire to transpose rituals and rhythms of monastic devotion, which encourage a highly cultivated interior and private spiritual life, onto the day-to-day life of a layperson. As spiritual guide, More's Life of Pico aims to produce a reflective, capable reader while at once setting the limits of his or her intellectual endeavor within narrowly fixed orthodox parameters.